The Effect of Good Corporate Governance on Company Value Moderated By Integrated Reporting - Permana, Sandi; Aruddy; Jahroh, Siti (School of Business, Bogor Agricultural University (SB-IPB), 2023)
This research examined the influence of good corporate governance (GCG) mechanisms and their relation to Integrated Reporting (IR) on company value in the BUMN sub-sector, consisting of banking and non-banking. The data used in this study were secondary in the form of time series sourced from the Central Statistics Agency (BPS) and the Indonesia Stock Exchange (IDX) in the period of 2017-2021. The number of companies analyzed in this study was 23 companies. The GCG components analyzed consisted of managerial ownership (KM), institutional ownership (KINS), and independent commissioners (KIND), as well as integrating reporting (IR) as moderating variables. Data processing in this study employed Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The findings show that non-bank and accumulative firms, institutional ownership variables, and independent commissioners all have a significant impact on firm value. Meanwhile, in banking firms, the variable of managerial ownership has a significant impact on firm value. The impact of GCG on company value has shifted significantly after being moderated by IR. In banking firms, one variable (KM) has a significant effect on firm value, whereas KINS and KIND have no significant effect, and even KINS has a negative interaction. KINS and KIND have a significant effect in non-bank companies, but only KINS has a positive effect. In absolute terms, the influence of IR is positive for KM and KIND, but has no significant implications for KINS. Keywords: company values, good corporate governance, integrated reporting, shareholders, state-owned enterprises